Analisis Pengelolaan Usaha Percetakan Untuk Meningkatkan Kepuasan Konsumen Pada CV. Antique Production Dalam Prespektif Ekonomi Islam - Puspa Indah Sari Pohan; Azhari Akmal Tarigan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The focus of this research is, 1) how business management at CV Antique Production to improve consumer satisfaction in the Islamic Perspective of Islam. 2) What are the constraints on printing business management at CV Antique Production in improving consumer satisfaction in the Islamic Emergency Perspective. 3) What are the solutions of the constraints on printing business management on CV antique production in improving consumer satisfaction in the Islamic Emergency Perspective. This research uses descriptive approach with the type of qualitative research. The data source obtained is primary and secondary data. Data collection techniques with observation, interview and documentation. Data analysis techniques use data reduction, data presentation, and concludes. This research is the management of printing business done by CV. Antique Production To improve consumer satisfaction in the Islamic economic perspective is to implement management functions or management in Islam well. The management function consists of: the implementation (planning), organizing), implementation (actuating), and control (controlling). Constraint business management facing by CV. Antique Production To improve consumer satisfaction include internal constraints that is lack of employees when many demand and delay of product raw material supplies, and external constraints are of unclear consumers with product details of the product and competitor or competitors. Solutions to overcome constraints on printing business management by CV. Antique Production To improve consumer satisfaction includes the solution of internal constraints that adds employees with freelance systems, adding more than one supplyer and check periodically inventory of product raw materials while solutions for external constraints are providing conservation sessions of the booking and consuming businesses by opening product gallery and developing its employee skills.